Abnormal activation of motor cortical network during phasic REM sleep in idiopathic REM sleep behavior disorder. Issue 2 (16th November 2018) - Sunwoo, Jun-Sang; Cha, Kwang Su; Byun, Jung-Ick; Kim, Tae-Joon; Jun, Jin-Sun; Lim, Jung-Ah; Lee, Soon-Tae; Jung, Keun-Hwa; Park, Kyung-Il; Chu, Kon; Kim, Han-Joon; Kim, Manho; et al.
Abstract: Study Objectives: We investigated electroencephalography (EEG) power spectral density and functional connectivity during phasic and tonic rapid eye movement (REM) sleep, and examined any differences between patients with idiopathic REM sleep behavior disorder (iRBD) and controls. Methods: EEG data from 13 people with iRBD (mean age, 66.3 years; men, 84.6%) and 10 controls (mean age, 62.3 years; men, 70%) were analyzed. We selected thirty 3 s miniepochs of both tonic and phasic REM sleep. We estimated relative power for six frequency bands. For functional connectivity analysis, we calculated weighted phase lag index (wPLI) and conducted pairwise comparisons between the two groups. Results: EEG power spectral analysis revealed significant interactions between the REM sleep state (phasic vs. tonic) and group at sigma ( p = 0.009) and beta ( p = 0.002) bands. Sigma- and beta-power decrease during phasic REM sleep was more pronounced and extensive in people with iRBD than in controls. Regarding functional connectivity, there were significant interactions between the REM sleep state and group at alpha ( p = 0.029), sigma ( p = 0.047), beta ( p = 0.015), and gamma ( p = 0.046) bands. The average wPLI was significantly higher during phasic REM sleep than during tonic REM sleep, which was observed in people with iRBD but not in controls. The altered functional connections mainly involved the frontal and parietal regions at beta and gamma bands. Conclusions: Our findings provide neurophysiological evidence for pathological motor cortex activation during phasic REM sleep which may be associated with generation of dream-enacting behaviors in iRBD.